The image of a Japanese as seen by a Dutchman in the English novel and its Ukrainian translation - Rebrii, Oleksandr (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
The article deals with the problem of rendering a literary image of a foreigner in translation. The object of research is the cumulative literary image of a Japanese on the material of David Mitchell’s novel “The Thousand Autumns of Jacob De Zoet” and the subject of research is the means and strategies of its reproduction in the Ukrainian translation. The aim of the research is to conceptualize the above strategies and determine the factors that have an impact on the translator’s decision-making. In particular, the attention is drawn to the factor of ethnic stereotypes that underline the formation of a foreigner’s image in a literary discourse. The article offers a hierarchic view of a literary image as an interaction of three levels of analysis: mega-image (correlated with the idea/theme/conception of a literary piece), macro-image (literary image per se) and micro-image (linguistic and/or stylistic means of a macro-image embodiment). Correspondingly, the translator’s attention should be concentrated on equivalent rendering micro-images, but in a manner consistent with corresponding macro-images and the mega-image of the whole text. Every literary image of a foreigner is based on certain ethno-stereotypes, also known as heterostereotypes that govern the author’s selection of micro-images and consequently the whole structure of a macro-image. Three aspects of a Japanese’s macro-image were singled out: appearance; speech characteristics; traditions, customs and rituals. At the next stage, the micro-images of these aspects’ verbalization were singled out and the translator’s strategies of their re-creation were analyzed. The conclusion was made that due to the similarity in foreigners’ stereotyping by the British and Ukrainians, the translator had no need for cultural adaptations and their strategy was predominantly aimed at overcoming interlinguistic asymmetry.